SOCIAL CONSCIOUSNESS AS A PHILOSOPHICAL CATEGORY IN THE CONTEXT OF DIGITAL COMMUNICATION - Sehen, Yaroslav (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2025)
The article provides a philosophical understanding of the category of social consciousness in the context of modern digital communication. Taking into account the transformational nature of the information society, the author proposes to consider social consciousness not as a static reflection of social existence, but as a dynamic and sensitive to technological changes form of collective spiritual existence. The relevance of the study is due to the need to rethink traditional philosophical concepts under the influence of new social and techno-communication realities. An interdisciplinary methodological approach is applied, combining elements of hermeneutics, phenomenology, critical social philosophy and techno-philosophy. The key stages of the evolution of ideas about social consciousness in Western and Ukrainian philosophical traditions are analyzed, and the main factors of its modern transformation are identified: virtualization of experience, fragmentation of information, algorithmization of communication, post-truth and the formation of new types of digital identity. Special attention is paid to the analysis of digital communication as not only a technological but also a socio-cultural phenomenon that affects the deep meanings of collective thinking. It is shown that digital communication constructs a new form of social consciousness - dynamic, unstable, reactive, sensitive to the information environment and manipulative strategies. The author concludes that social consciousness in the digital age appears simultaneously as a space of threat (due to the weakening of criticality, the growth of emotional reactivity, information overload), and as a space of new opportunities (for mobilization, self-identification, resistance). The article emphasizes the importance of further philosophical understanding of the processes occurring at the intersection of technology and consciousness, in particular in the context of information warfare and the global struggle for meanings.